RAHMAT DALAM MISTERI INKARNASI ALLAH PUTRA DALAM TRADISI PATRISTIK DAN SKOLASTIK: TELAAH SHEEBEN SERTA KEBARUANNYA - GUNAWAN, THEODORUS CHRISTIAN (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2022)
Theological reflection is constantly developing an understanding of Revelation. TheMystery of Revelation basically remains forever. One of those mysteries is the graceof the Incarnation of the Son of God. The theme of grace itself is a subject that hasbeen widely discussed throughout the history of the development of Catholictheology. One of the modern theologians who discuss grace in the Incarnation of theSon of God is Matthias Joseph Scheeben. He discusses this theme in an article in hisbook entitled Le meraviglie della grazia divina. Scheeben's uniqueness in exploringgrace in the Incarnation of the Son of God is that he always quotes reflections fromboth Patristic and Scholastic theologians. Through such elaboration, he then finds anew reflection and understanding of Grace in the Mystery of the Incarnation of theSon of God. This is what enriches the theological treasures of the Catholic Church.